Arterial Stiffness and Vascular Aging: Effects of Hypertension - E. S. Fomina; V. S. Nikiforov (Архивъ внутренней медицины)
This review highlights the relationship of age and arterial hypertension observed in the aging process. The main structural and functional changes underlying the increase in vascular stiffness are analyzed. The similarity of vascular changes in aging and arterial hypertension was noted. The negative effect of increased central blood pressure on target organs is considered. Attention is paid to the analysis of arterial stiffness as a marker of vascular aging. The parameters of the carotid-femoral pulse wave propagation velocity, the cardio-ankle vascular index (CAVI), the ankle-brachial index, the finger-brachial index, and the augmentation index were examined separately. The prognostic and clinical value of the parameters of vascular stiffness is considered. In particular, the clinical guidelines for arterial hypertension report the need to use arterial stiffness indicators to improve the accuracy of cardiovascular risk stratification, especially in medium-risk patients. Measurement of vascular stiffness and central aortic pressure should be recommended as one of the methods for stratifying cardiovascular risk in patients with intermediate SCORE risk, as well as in those whose target organ damage was not detected by routine methods. The article also notes the independent diagnostic and prognostic value of the CAVI.